2007
DOI: 10.1021/ja074536x
|View full text |Cite
|
Sign up to set email alerts
|

PtCl2-Catalyzed Rapid Access to Tetracyclic 2,3-Indoline-Fused Cyclopentenes:  Reactivity Divergent from Cationic Au(I) Catalysis and Synthetic Potential

Abstract: Au catalysts have attracted much attention lately owing to their unique capacity in activating π systems for various useful transformations. 1 Pt catalysts, mostly PtCl 2 , often catalyze, to a varying extent, similar reactions. 2 Examples of divergent reactivities of these two different metals are rare. 3 Herein, we report a PtCl 2 -catalyzed highly selective formation of 2,3-indoline-fused cyclopentenes from propargylic 3-indoleacetates, in sharp contrast to our previously reported Au I -catalyzed cyclobutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(56 citation statements)
references
References 14 publications
1
55
0
Order By: Relevance
“…Thus, cases of divergent reactivity between gold and platinum catalysts are intriguing. [178] One example highlighting this concept was reported by Fensterbank, Malacria, and coworkers. [179] While examining the reactivity of hydroxylated 1,5-alleneynes, they found that Pt and Au catalysts operate completely differently when given a choice to activate one of two p systems.…”
Section: Selecting Between Carbon-carbon Coupling Reactionsmentioning
confidence: 92%
“…Thus, cases of divergent reactivity between gold and platinum catalysts are intriguing. [178] One example highlighting this concept was reported by Fensterbank, Malacria, and coworkers. [179] While examining the reactivity of hydroxylated 1,5-alleneynes, they found that Pt and Au catalysts operate completely differently when given a choice to activate one of two p systems.…”
Section: Selecting Between Carbon-carbon Coupling Reactionsmentioning
confidence: 92%
“…We recently discovered that the [{Rh(CO) 2 Cl} 2 ] catalyst was able to promote 1,3 acyloxy migration of propargyl esters to form allenes; [8] this transformation was previously realized mainly by π-acidic metal-based catalysts such as silver, [9, 10] copper, [911] platinum, [11, 12] and gold [10, 13] in various cascade reactions. [14, 15] Given this novel reactivity of [{Rh(CO) 2 Cl} 2 ] for the promotion of 1,3 acyloxy migration and its well-known capability to undergo oxidative addition and reductive elimination, we envisioned that alkylidene cycloheptadiene 3 could be prepared directly from readily available cyclopropane 1 [16] in the presence of the [{Rh(CO) 2 Cl} 2 ] catalyst.…”
mentioning
confidence: 99%
“…[11] The corresponding transformations were reported in the b-hydroxyallene series. [12] These reactions came to completion within 1 h in CH 2 Cl 2 at room temperature.…”
Section: Resultsmentioning
confidence: 97%